Development in Venezuela of energy system based in the hydrogen. Part IV: End Uses - Posso, Fausto; Contreras, Alfonso (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The stage of Final Uses of a renewable energy system is studied with the H2 like energy vector, by means of the formulation of a model mathematical representative semi empiric of the main technical and economic aspects involved in the operation of the cells of combustible PEM, transformation technology selected to provide from energy to rural towns of Venezuela located in the parish Trinidad of the Chapel of the Portuguese state. The simulation embraces a 20 year-old horizon, considering the increment in the energy demand and the decrease in the unitary costs of the cells of fuel. The results show that the main operation variables: current density, efficiency and voltage present the typical behavior of this type of cells, while from the economic point of view, the cost of the produced electricity diminishes continually for effects of the scale economy. The use of the cells PEM to provide from energy to population”™s rural Venezuelan sectors is viable in principle when contributing to the improvement of the quality of life and sustainable development of these isolated and depressed regions, those which, for its distance of the development of these isolated and depressed regions, those which, for its distance of the electric net and surface that embrace, they have not been covered by the electric net.